Reflections - Wing, Foong Chew (Persatuan Pustakawan Malaysia, 2012)
After 5 years of teaching in a secondary school where I enjoyed being with students and participating in their activities, I became a professional librarian in 1976. In the early years of librarianship in Malaysia, local librarians had to obtain their professional qualifications from abroad, until library schools were established in Malaysia from 1968 onwards. I began my PPM (Persatuan Perpustakaan Malaysia = Library Association of Malaysia) part-time course in 1972 and took The Library Association (British) examinations. Only 10% of the class of 70 students made it to the end. At this juncture, it is fitting to recognize the role and achievements of the pioneer Malaysian librarians who established PPM in 1955 with the objectives of pursuing librarianship as a recognized profession by the Government, setting up the National Library and State Public Libraries, and working towards the establishment of library schools in universities.